Evolving role of MRI in optimizing the treatment of multiple sclerosis: Canadian Consensus recommendations. (5th June 2015) - Arnold, Douglas L; Li, David; Hohol, Marika; Chakraborty, Santanu; Chankowsky, Jeffrey; Alikhani, Katayoun; Duquette, Pierre; Bhan, Virender; Montanera, Walter; Rabinovitch, Hyman; Morrish, William; Vandorpe, Robert; et al.
Background: Magnetic resonance imaging (MRI) is increasingly important for the early detection of suboptimal responders to disease-modifying therapy for relapsing–remitting multiple sclerosis. Treatment response criteria are becoming more stringent with the use of composite measures, such as no evidence of disease activity (NEDA), which combines clinical and radiological measures, and NEDA-4, which includes the evaluation of brain atrophy. Methods: The Canadian MRI Working Group of neurologists and radiologists convened to discuss the use of brain and spinal cord imaging in the assessment of relapsing–remitting multiple sclerosis patients during the treatment course. Results: Nine key recommendations were developed based on published sources and expert opinion. Recommendations addressed image acquisition, use of gadolinium, MRI requisitioning by clinicians, and reporting of lesions and brain atrophy by radiologists. Routine MRI follow-ups are recommended beginning at three to six months after treatment initiation, at six to 12 months after the reference scan, and annually thereafter. The interval between scans may be altered according to clinical circumstances. Conclusions: The Canadian recommendations update the 2006 Consortium of MS Centers Consensus revised guidelines to assist physicians in their management of MS patients and to aid in treatment decision making.